Talleres de dramatización para estimular el control de conductas agresivas - Arias Flores, Adelita Jackeline (2021)
The present work of professional sufficiency has been carried out with the purpose of deepening and addressing one of the main problems that we have in society, which are aggressive behaviors, so we are going to present some strategies to form aggressive behaviors through values that can help us to reduce this type of attitudes in children of the initial level of 5 years of IE N ° 1660 "Garatea" -Nuevo Chimbote. For this, we propose as purposes of our work to know the theoretical foundation of non aggressive behaviors and to propose dramatization workshop sessions within the communication approach, communication area of the national curricular program, which allow a decrease in aggressive behaviors in 5-year-old students and thus promote a more relevant and coherent pedagogical practice. The present work of professional sufficiency, for a better organization and presentation, has: theoretical part, pedagogical support, conclusions, bibliographic references and their corresponding annexes.